Fair Competition and Inclusion in Sport: Avoiding the Marginalisation of Intersex and Trans Women Athletes - Jonathan Cooper (Philosophies, 2023)
Despite the reality of intersex individuals whose biological markers do not necessarily all point towards a traditional binary understanding of either male or female, the vast majority of sports divide competition into categories based on a binary notion of biological sex and develop policies and regulations to police the divide. In so doing, sports governing bodies (SGBs) adopt an imperfect model of biological sex in order to serve their particular purposes, which, typically, will include protecting the fundamental sporting value of fair competition. Yet, one potential consequence of enforcing such an approach would seem to be the exclusion or marginalization of individuals whose biological development does not fit within the binary model, whether due to genetics or through a choice to undergo medical intervention to better represent a chosen gender identity. Any such exclusion or marginalization will inevitably tend to undermine another fundamental value of sport, that of inclusivity. In the context of those with differences of sex development, SGBs appear to be faced with a difficult problem: dealing with a conflict between two fundamental values of sport. Different approaches to this problem have been suggested, with some academics proposing that sports organisations, in general, ought to prioritise fairness above, while others suggest the need to ‘balance’ competing values or even to prioritise inclusion over fairness. However, it is argued that any of these approaches are, in principle, justifiable as any sport should be free to prioritise or balance its own values. What seems more important for any SGB is the need for a rational and transparent justification of regulations that pursue fair competition at the expense of inclusivity. Furthermore, where fair competition and inclusivity are fundamental values, any such justification would seem to demand adherence to some basic norms. First, the regulations should be built on (and articulate) a consistent and principled basis of what ‘fair competition’ means in a particular sport. Second, any regulations should only exclude or restrict participation to the minimum degree necessary to achieve the sense of fair competition so articulated. Third, SGBs should be transparent about what their values are and where their priorities lie so that participants and other stakeholders are able to make an informed choice as to whether they wish to participate in, support, or be associated with a particular sport. With reference to the adoption of the Eligibility Regulations for Athletes with Differences of Sex Development (the ‘DSD Regulations’) by the International Association of Athletic Federations (IAAF), this article seeks to evaluate whether the approach of the IAAF satisfied these basic requirements.